Recent dynamics of arctic and sub-arctic vegetation - Epstein, Howard E; Myers-Smith, Isla; Walker, Donald A (Environmental research letters, 2013)
We present a focus issue of Environmental Research Letters on the 'Recent dynamics of arctic and sub-arctic vegetation'. The focus issue includes three perspective articles (Verbyla 2011 Environ. Res. Lett. 6 041003, Williams et al 2011 Environ. Res. Lett. 6 041004, Loranty and Goetz 2012 Environ. Res. Lett. 7 011005) and 22 research articles. The focus issue arose as a result of heightened interest in the response of high-latitude vegetation to natural and anthropogenic changes in climate and disturbance regimes, and the consequences that these vegetation changes might have for northern ecosystems. A special session at the December 2010 American Geophysical Union Meeting on the 'Greening of the Arctic' spurred the call for papers. Many of the resulting articles stem from intensive research efforts stimulated by International Polar Year projects and the growing acknowledgment of ongoing climate change impacts in northern terrestrial ecosystems.